Antrodia cinnamomea induces autophagic cell death via the CHOP/TRB3/Akt/mTOR pathway in colorectal cancer cells. Issue 1 (December 2018) - Tsai, Dai-Hua; Chung, Cheng-Han; Lee, Kung-Ta
Abstract Antrodia cinnamomea, a well-known traditional medicine used in Taiwan, is a potent anticancer drug for colorectal cancer, but the upstream molecular mechanism of its anticancer effects remains unclear. In this study, A. cinnamomea extracts showed cytotoxicity in HCT116, HT29, SW480, Caco-2 and, Colo205 colorectal cancer cells. Whole-genome expression profiling ofA. cinnamomea extracts in HCT116 cells was performed.A. cinnamomea extracts upregulated the expression of the endoplasmic reticulum stress marker CHOP and its downstream gene TRB3. Moreover, dephosphorylation of Akt and mTOR as well as autophagic cell death were observed. Gene expression and autophagic cell death were reversed by the knockdown of CHOP and TRB3. Autophagy inhibition but not apoptosis inhibition reversedA. cinnamomea -induced cell death. Finally, we demonstrated thatA. cinnamomea extracts significantly suppressed HCT116 tumour growth in nude mice. Our findings suggest that autophagic cell death via the CHOP/TRB3/Akt/mTOR pathway may represent a new mechanism of anti-colorectal cancer action byA. cinnamomea .A. cinnamomea is a new CHOP activator and potential drug that can be used in colorectal cancer treatment.